The enzymatic processing of α-dystroglycan by MMP-2 is controlled by two anchoring sites distinct from the active site. - Magda Gioia; Giovanni Francesco Fasciglione; Diego Sbardella; Francesca Sciandra; MariaLuisa Casella; Serena Camerini; Marco Crescenzi; Alessandro Gori; Umberto Tarantino; Paola Cozza; Andrea Brancaccio; Massimo Coletta; et al. (PLoS ONE, 2018)
Dystroglycan (DG) is a membrane receptor, belonging to the dystrophin-glycoprotein complex (DGC) and formed by two subunits, α-dystroglycan (α-DG) and β-dystroglycan (β -DG). The C-terminal domain of α-DG and the N-terminal extracellular domain of β -DG are connected, providing a link between the extracellular matrix and the cytosol. Under pathological conditions, such as cancer and muscular dystrophies, DG may be the target of metalloproteinases MMP-2 and MMP-9, contributing to disease progression. Previously, we reported that the C-terminal domain α-DG (483-628) domain is particularly susceptible to the catalytic activity of MMP-2; here we show that the α-DG 621-628 region is required to carry out its complete digestion, suggesting that this portion may represent a MMP-2 anchoring site. Following this observation, we synthesized an α-DG based-peptide, spanning the (613-651) C-terminal region. The analysis of the kinetic and thermodynamic parameters of the whole and the isolated catalytic domain of MMP-2 (cdMMP-2) has shown its inhibitory properties, indicating the presence of (at least) two binding sites for the peptide, both located within the catalytic domain, only one of the two being topologically distinct from the catalytic active groove. However, the different behavior between whole MMP-2 and cdMMP-2 envisages the occurrence of an additional binding site for the peptide on the hemopexin-like domain of MMP-2. Interestingly, mass spectrometry analysis has shown that α-DG (613-651) peptide is cleavable even though it is a very poor substrate of MMP-2, a feature that renders this molecule a promising template for developing a selective MMP-2 inhibitor.